Legal Aspect of Sporadic Implementation of Petama Land Registration Based On Government Regulation Number 24 of 1997 Concerning Land Registration in Cirebon City - Susanti Susanti (Sultan Agung Notary Law Review, 2020)
The data recorded and written in a certificate must be free from a typo or an error in the data collection on the land object in question, meaning that both physical data and juridical data of its existence can be guaranteed legal protection. Legal protection guarantees in land registration are that the owner of the certificate does not easily get interference or lawsuits from other parties, the certificate owner can defend his rights from interference or lawsuits from other parties. The purpose of this study To know Implementation of sporadic land registration for the first time on uncertified land at the Ciebon City Land Office and Application of the principle of safe sporadic implementation of land registration for the first time at the Cirebon City Land Office? The method used in this research is sociological juridical method, the specification in this research is descriptive analytic, the data used are primary data and secondary data, using data collection by interview and literature study, qualitative data analysis, problems analyzed by theory, legal certainty and Theory of Justice. The results of this study indicate that the first sporadic implementation of land registration can be submitted by the right holder or through proxies to the Land Office. Meanwhile, the method of the community in carrying out land registration is carried out sporadically. For people who carry out sporadic land registration, it can be done directly by the land owner or through the PPAT Office.The application of the safe and open principle at the Cirebon City Land Office is not in accordance with what was expected, where in the implementation of the principle of safety, the Land Office was not thorough and careful in processing the physical data files and juridical data of the applicant.